Respostas
respondido por:
2
Olá!
3x - 4y = -7 (como o X = 3, substitua o 3 no lugar do x)
3.3 - 4y = -7
9 - 4y = -7
-4y = -7 -9 (sempre que mudar o número de lado da igualdade, inverta o sinal)
-4y = -16
y = -16 / -4
y = 4
3x - 4y = -7 (como o X = 3, substitua o 3 no lugar do x)
3.3 - 4y = -7
9 - 4y = -7
-4y = -7 -9 (sempre que mudar o número de lado da igualdade, inverta o sinal)
-4y = -16
y = -16 / -4
y = 4
vitorsantos95:
obrigado
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás